Natural crop protection in the tropics: Letting information come to life - Stoll, G. (AGRECOL / CTA / Margraf Verlag, 2000)
The success of earlier editions encouraged the author to produce this revised edition. In addition to discussing methods of field and storage protection, she includes case-studies illustrating ways to verify and adapt natural protection techniques.